(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the poetics of Alisher Navoi’s poem “Hayrat ul-Abror” in the ontological and epistemological aspect , based on the relations of Farhad and Shirin, Layli and Majnun. The idea of monotheism, expressed in the essence of the figurative, the idea of tawhid as a result of the degree of knowledge, the image of a witness (shahada) determines the poet’s ontological system. The philosophical and theological foundations of the interpretation and analysis of a literary text as a personal experience of the poet based on the Islamic charter, its unique perception of theology and the Universe are studied. The amazement of the Sufi traveler reflects an important synergetic strategy of cognition: an approach to the relations of two interconnected worlds, phenomenal and spiritual, as two sides of one.